Electronic Information Systems and Human Services Organisations: Avoiding the Pitfalls of Participatory Design. - Gillingham, Philip (British Journal of Social Work, 2015)
Recent research and evaluation of the forms of electronic information systems (IS) being used in child welfare agencies in both Australia and England and Wales have shown that, despite the many millions of dollars spent, not only are they unfit for purpose, but also they may undermine front line practice. Jurisdictions may differ in their readiness to accept and respond to these criticisms, but attention is now turning to how IS can be designed that do meet the needs of practitioners. A particular problem that has been identified is the limited involvement that practitioners have had in the design of I Sand efforts are now being made to include them. Though there is a considerable amount of literature about how to include the intended users of technology in designing IS, there is a paucity of advice that is relevant to the particular circumstances of social work and social care practitioners. Drawing from an ethnographic study of an IS implementation project in a human services organisation, this article aims to begin to address this gap in the literature by articulating some of the pitfalls for social workers and other human services staff who may become involved in the design, or redesign, of IS.